Working with text in CLIL as an incentive for developing reading skills. A study on teaching history in a foreign language. - Lazar, Jolanda (Anali PAZU HD, 2022)
Poor reading comprehension resulting from lack of student motivation is a major pedagogical problem. According to constructivist principles, language teaching is based on active use of language in authentic situations. This view of teaching and learning entails different approaches. Content and language integrated learning is gaining traction in Europe and worldwide as an alternative methodical approach. Research indicates a positive effect of CLIL on reading comprehension and the development of reading strategies. This article provides an overview of works by the method of CLIL and presents a case study.
Keywords: constructivism; reading strategies; motivation; content and language integrated learning